The effect of time interval between antenatal corticosteroid administration and delivery on outcomes in late preterm neonates born to mothers with diabetes: a retrospective cohort study - Li, Xiaoyu; Zhang, Jing; Hao, Qingfei; Du, Yanna; Cheng, Xiuyong (Frontiers in Pediatrics, 2023)
Objectives The study aims to investigate whether the time interval between administering antenatal corticosteroids (ACS) and delivery influences the neonatal outcomes in late preterm (LPT) neonates (34 + 0 to 36 + 6 weeks) born to mothers with diabetes. Study design This retrospective cohort study included women with any type of diabetes who gave birth between 34 + 0 weeks and 36 + 6 weeks of gestation. Based on the time interval between the first dose of corticosteroid and delivery, the cases were stratified into the following groups: <2, 2–7, and >7 days. Women unexposed to ACS served as the control group. The primary outcomes included the incidence of neonatal hypoglycemia and respiratory distress syndrome/transient tachypnea of the newborn. Multivariate logistic regression was used to assess the relationship between the time interval and neonatal outcomes and adjust for potential confounders. Results The study enrolled a total of 636 parturients. Among them, 247 (38.8%) delivered within 2 days after ACS administration, 169 (26.6%) within 2–7 days, and 126 (19.8%) at >7 days. Baseline characteristics such as type of diabetes, methods of glycemic control, preterm premature rupture of membrane, placenta previa, cesarean delivery, indication for delivery, percentage of large for gestational age, birth weight, and HbA1c in the second or third trimester were significantly different among the four groups. The multivariate analysis showed no statistically significant difference in the incidence of primary or secondary neonatal outcomes between the case and control groups. Conclusions ACS treatment was not associated with neonatal hypoglycemia and respiratory outcomes in LPT neonates born to diabetic mothers, regardless of the time interval to delivery.